Information Characteristics and Errors in Expectations: Experimental Evidence - Constantinos Antoniou; Glenn Harrison; Morten Lau; Daniel Read (Institute for the Study of Labor (IZA), 2015)
We design an experiment to test the hypothesis that, in violation of Bayes Rule, some people respond more forcefully to the strength of information than to its weight. We provide incentives to motivate effort, use naturally occurring information, and control for risk attitude. We find that the strength-weight bias affects expectations, but that its magnitude is significantly lower than originally reported. Controls for non-linear utility further reduce the bias. Our results suggest that incentive compatibility and controls for risk attitude considerably affect inferences on errors in expectations.
Keywords: D81; D84; G11; 330; behavioral biases; market efficiency; experimental finance